(untitled) (Revista Contexto & Educação, 2022)
Star Wars is a science fiction franchise, created by George Lucas and categorized as space opera, which has remained with a legion of fans for generations. The article aims to highlight concepts of philosophy and political science that can be worked from the episodes of the Star Wars Saga, considering the organization of films based on concept-images. As a methodological procedure, we selected all the film episodes in the saga. For that, it was necessary to understand the Star Wars saga as film-texts, the textual film analysis being anchored in Vanoye and Goliot-Lété. As a result, we present content and philosophical themes that can be worked on, starting from the saga, considering the guiding documents of basic education of high school level. “May the force be with you”!